Student Satisfaction with Thesis Guidance Service of the Mechanical Engineering Education Study Program, University of Palangka Raya - Lumbantobing, Marko Ayaki (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
This study aims to determine student satisfaction with thesis guidance services by lecturers in the Mechanical Engineering Education Study Program, Palangka Raya University using a survey method through 5 aspects of satisfaction namely availability, mastery of material substance, mastery of thesis writing techniques, facilities, and thesis completion process. Data analysis techniques in this study used descriptive statistics. by measuring using a Likert scale. The sample in this study were students from class 2015, 2016, 2017 and 2018 who were conducting thesis guidance at the UPR Mechanical Engineering Education Study Program, a total of 32 people. The instrument used in this study was a questionnaire with 4 (four) answer choices in terms of 5 aspects, namely availability, mastery of the substance of the material, mastery of writing techniques, facilities and completion processes. The results showed that the thesis guidance service in the Mechanical Engineering Education Study Program was at a satisfaction index of 3.25, which was in the satisfied category.